1994
DOI: 10.1093/oxfordjournals.aje.a117182
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-reported Hospital Admission in a Prospective Study

Abstract: This study examines the validity of self-reported hospital admission data obtained by telephone interview from a sample of 563 participants in a follow-up study in Auckland, New Zealand. The personal recall of hospital admissions over a 4-year period between 1988 and 1991 was compared with a national computerized record of all hospital admissions. Only two admissions were recalled by participants but not recorded on the hospital record. However, the study found significant underreporting of admissions by parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…Conversely, parents with high socioeconomic status were significantly better reporters of their children's ADHD outpatient services compared to parents with low socioeconomic status when parent reports were compared to medical records [12]. However, other studies have found that the agreement between self-reported and computer database data for health care utilization is affected little by education and social class [22][23][24]. The lack of a statistically significant difference in agreement between high and low values for demographic characteristics in the present study may be related to the cut-point selected for comparing agreement.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, parents with high socioeconomic status were significantly better reporters of their children's ADHD outpatient services compared to parents with low socioeconomic status when parent reports were compared to medical records [12]. However, other studies have found that the agreement between self-reported and computer database data for health care utilization is affected little by education and social class [22][23][24]. The lack of a statistically significant difference in agreement between high and low values for demographic characteristics in the present study may be related to the cut-point selected for comparing agreement.…”
Section: Discussionmentioning
confidence: 98%
“…Differences have been noted in the reporting of physician consultations, hospital admissions and specific procedures such as Pap tests (Glandon, Counte et al 1992;McCullum, Lonergan et al 1993;Marshall, Grayson et al 2001;Norrish, North et al 1994;Hancock, Sanson-Fisher et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…Although other studies [15] have used hospitalizations reported by the patients themselves, we were constrained to use the caregiver as the resource, given the methodology used in this study. To our knowledge, there are no studies with which to compare our results.…”
Section: Discussionmentioning
confidence: 99%